CONCEPTUAL METAPHORS IN 'MAHFUDZAT': THE REPRESENTATION OF KNOWLEDGE VALUES IN ARAB SOCIETY - Alfina Rob'iah Adawiyah; Ni Gusti Ayu Roselani; Aris Romadhon; Deni Ferdiansa; Dini Gilang Sari; Annisa Nurhijatul Kania (Leksema: Jurnal Bahasa dan Sastra, 2025)
This study aimed to identify the forms of metaphor in Mahfudzat's work on knowledge and to prove that the work reflects the life of Arab society. Lakoff and Johnson's (2003) theory were used as the base for data analysis. The theory states that there are source and target domains in metaphor which are described in this study by using Kovesces' mapping table. As this is a descriptive-qualitative research, the data of this study are in the forms of textual materials of Mahfudzat from Modern Islamic Boarding school Darussalam Gontor. The data source is limited to Mahfudzat materials containing the word ‘knowledge’ in the curricula for Grade 1 and 2. For collecting the data, documentation techniques were applied by reading and understanding the text as well as identifying, classifying, and categorizing the data. Meanwhile, the process of data analysis went through several stages i.e.: reading, composing metaphors, describing conceptual metaphor mapping, categorizing the types of metaphors, and drawing conclusions. The results show that there are 13 data related to science in Mahfudzat. In addition, 8 data containing metaphors were found, comprising 2 structural metaphors, 1 orientational metaphor, and 5 ontological metaphors.